From beliefs to practices: University English lecturers’ digital technology integration in a regional Vietnamese context - Dang Thi Bao Dung; Lanh Le Van; Du Tran; The Nguyen Huu (English Language Teaching Educational Journal, 2026)
Digital technology integration has become a central feature of English language teaching (ELT) in higher education, yet how lecturers translate positive beliefs into classroom practices remains uneven, especially in underrepresented regional settings. This qualitative study examines how university English lecturers in the Mekong Delta, Vietnam, a socio-economically diverse region where national digital transformation agendas are mediated by local infrastructural and pedagogical constraints, move from beliefs to practices in integrating digital technologies into ELT. Semi-structured interviews were conducted with 14 purposively selected lecturers and analyzed thematically through an inductive-deductive approach. The findings reveal broad endorsement of technology’s pedagogical value alongside marked variation in instructional and assessment enactments. Lecturers’ adoption patterns are best understood along a continuum from high adopters to emerging and minimal users, shaped by pedagogical orientation, perceived usefulness and ease of use, assessment literacy, and contextual and institutional conditions. The study sharpens teacher cognition research by showing that the belief-practice relationship is non-linear and mediated, and by conceptualizing technology adoption as a continuum rather than a fixed typology in a regional ELT context in higher education. Implications are discussed for professional development, institutional support, and sustainable digital transformation in ELT.